The Body in Adult Education: Introducing a Somatic Learning Model - Tara L. Horst (Adult Education Research Conference, 2008)
This paper explores the nature and definitions of somatic knowing, presents a model explaining the aspects of somatic learning, and suggests how somatic learning/ knowing can be incorporated into the practice of adult education.
Keywords: somatic learning; body; women; managers